Regiospecificity of Chlorophenol Reductive Dechlorination by Vitamin B(12s) - Smith, Mark H. (1994)
Vitamin B(12), reduced by titanium (III) citrate to vitamin B(12s), catalyzes the reductive dechlorination of chlorophenols. Reductive dechlorination of pentachlorophenol and of all tetrachlorophenol and trichlorophenol isomers was observed. Reaction of various chlorophenols with vitamin B(12) favored reductive dechlorination at positions adjacent to another chlorinated carbon, but chlorines ortho to the hydroxyl group of a phenol were particularly resistant to reductive dechlorination, even if they were also ortho to a chlorine. This resulted in a reductive dechlorination pattern favoring removal of para and meta chlorines, which differs substantially from the pattern exhibited by anaerobic microbial consortia.